The disproportionate burden of pulmonary arterial hypertension among the elderly: global, regional, and national trends from 1990 to 2021—findings from the 2021 global burden of disease study - Tang, Meng; Liu, Xingxing; Hao, Xiaoyu; Liu, Zhiming; Li, Zuwei; Luo, Hanbin; Zou, Guohui (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesPulmonary arterial hypertension (PAH) is a chronic vascular disorder characterized by elevated pulmonary artery pressure and pulmonary vascular resistance, leading to right ventricular failure. This condition imposes a substantial economic burden and significant health challenges globally. This study aimed to comprehensively analyze the global burden of PAH, with specific attention to vulnerable populations including the elderly, by evaluating gender, age (especially older age groups), region, country, and sociodemographic variables using data from the Global Burden of Disease Study (GBD) 2021.MethodsUtilizing GBD 2021 data, we assessed the global, regional, and national burden and trends of PAH through metrics like age-standardized prevalence, mortality, and disability-adjusted life years (DALYs). Analyses included decomposition, health inequality, and frontier analysis. Age-period-cohort (APC) modeling was used to examine period and cohort effects (1990–2021), and future burden was projected using Bayesian APC (BAPC) modeling.ResultsIn 2021, while PAH prevalence and mortality counts were higher than previous years, age-standardized rates (prevalence—ASPR, mortality—ASMR/ASDR) and DALYs showed a declining trend. Crucially, the disease burden was significantly higher among females and, notably, the elderly population compared to males and younger age groups. Low Socio-Demographic Index (SDI) regions consistently bore a disproportionately higher burden of mortality and DALYs. Decomposition analysis identified population growth and population aging as major drivers of the overall PAH burden. Age-period-cohort effects confirmed that disease risk increased substantially with advancing age. BAPC projections suggest a potential decrease in the global PAH burden by 2035.ConclusionsProgress in reducing the PAH disease burden during 1990–2021 was limited globally, nationally, and regionally. This lack of progress was particularly pronounced among women and, critically, older age groups. Diagnosis, treatment, and prevention strategies remain critically insufficient in low- and middle-income countries. Therefore, proactively developing health policies tailored to the PAH disease burden—with specific consideration for the growing elderly population and aligned with national/regional economic development—is essential to address this major public health challenge.